A Democratic Rentier State? Taxation, Aid Dependency, and Political Representation in Benin - Giulia Piccolino (German Institute of Global and Area Studies (GIGA), 2014)
Drawing on the history of statebuilding in Western Europe, fiscal sociology has proposed the existence of a mutually reinforcing effect between the emergence of representative government and effective taxation. This paper looks at the case of Benin, a low-income West African country that underwent a fairly successful democratization process in the early 1990s. It finds, in contrast to previous studies that have emphasized dependency on aid rents, that Benin appears to have reinforced its extractive capacities since democratization. However, the effect of democratization has been largely indirect, while other factors, such as the influence of the International financial Institutions (IFIs) and the size of the country's informal sector, have played a more direct role in encouraging or inhibiting tax extraction. Nevertheless, the hypothesis that effective taxation depends on a quasiconsensual relationship between government and taxpayers finds some confirmation in the Beninese case.
Keywords: 300; Benin; taxation; rentier state; fiscal sociology; statebuilding; democracy; democratization